Perceived benefits, costs, and relationships on provincial doctors’ inclination to participate in urban–rural medical consortia in Central China: a social exchange theory perspective - Zhang, Bowen; Ma, Liang; Ma, Wenjie; Kang, Dingding; Mao, Yiqing (Frontiers in Public Health, 2025)
ObjectiveThis study aims to investigate the perceived benefits, costs, and relationships that influence doctors’ inclination to participate in urban–rural medical consortia (URMC). Furthermore, the study analyzes how perceived relationships moderate the impact of perceived benefits and costs on the inclination to take part in URMC.MethodsThe study was conducted between September 2022 and June 2023 utilizing an online survey in Henan Province, Central China, which included 749 respondents from provincial hospitals. Chi-square and hierarchical logistic regressions were used to determine the perceived factors of the participants’ inclination.ResultsThe study indicated that 85.4% doctors demonstrated a strong inclination to participate. Doctors who perceived significant financial benefits, non-financial benefits, and relationships had a high level of inclination to participate. Doctors who perceived high executive costs and technical costs were less likely to express a high level of inclination to participate. When doctors perceived a strong relationship, the influence of perceived non-financial benefits on their inclination to participate tended to be weaker.ConclusionThis study enhances the understanding of physicians’ motivations for participating in URMC and may inform program leadership and policymakers concerned with developing or enhancing rural medical services. It is essential for managers to enhance incentive mechanisms, strive to minimize both actual and perceived costs, and facilitate the establishment of high-quality professional relationships between provincial physicians and their counterparts in county-level healthcare institutions.